2021
DOI: 10.1016/j.jaci.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma sTIM-3 levels in patients with severe COVID-19

Abstract: Background: The pathogenesis of coronavirus disease 2019 (COVID-19) is still incompletely understood, but it seems to involve immune activation and immune dysregulation. Objective: We examined the parameters of activation of different leukocyte subsets in COVID-19-infected patients in relation to disease severity. Methods: We analyzed plasma levels of myeloperoxidase (a marker of neutrophil activation), soluble (s) CD25 (sCD25) and soluble T-cell immunoglobulin mucin domain-3 (sTIM-3) (markers of T-cell activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Ueland et al recapitulate the findings by Diao et al and report that sTIM-3, an exhaustion marker associated with chronic infections including HIV, Hepatitis B, Hepatitis C, and pulmonary tuberculosis, had a rise in expression in severe (ICU) patients, which correlated with the measured degree of pulmonary infiltration and the cardiac marker NTproBNP (16). Ueland et al hypothesize that T cells are traveling to these organs and are responsible for their harm, but temporarily upregulate sTIM-3 as "a mechanism to prevent persistent and overshooting T-cell activation, which could harm the host" (16). They still, however, claim their findings suggest that T-cell activation and exhaustion play a role in Covid-19 and posit T-cell targeted treatment options may be of interest (16).…”
Section: Dissecting Possible T Cell Migration "Exhaustion" and End supporting
confidence: 56%
See 2 more Smart Citations
“…Ueland et al recapitulate the findings by Diao et al and report that sTIM-3, an exhaustion marker associated with chronic infections including HIV, Hepatitis B, Hepatitis C, and pulmonary tuberculosis, had a rise in expression in severe (ICU) patients, which correlated with the measured degree of pulmonary infiltration and the cardiac marker NTproBNP (16). Ueland et al hypothesize that T cells are traveling to these organs and are responsible for their harm, but temporarily upregulate sTIM-3 as "a mechanism to prevent persistent and overshooting T-cell activation, which could harm the host" (16). They still, however, claim their findings suggest that T-cell activation and exhaustion play a role in Covid-19 and posit T-cell targeted treatment options may be of interest (16).…”
Section: Dissecting Possible T Cell Migration "Exhaustion" and End supporting
confidence: 56%
“…Ueland et al hypothesize that T cells are traveling to these organs and are responsible for their harm, but temporarily upregulate sTIM-3 as “a mechanism to prevent persistent and overshooting T-cell activation, which could harm the host” ( 16 ). They still, however, claim their findings suggest that T-cell activation and exhaustion play a role in Covid-19 and posit T-cell targeted treatment options may be of interest ( 16 ). Varchetta et al report an increase in TIM-3 and CD69 expression in CD8+ T cells and note the extent of CD8+ T cell lymphopenia was significantly greater in patients that succumbed to Covid-19 ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of 8 soluble checkpoint molecules including PD-1 and TIM-3 were negatively correlated with absolute counts of total, CD4, and CD8 T cells but not neutrophil counts, and TIM-3 was identified to have good predictive value for COVID-19 progression. Ueland et al confirmed the association between levels of soluble TIM-3 and COVID-19 severity [ 44 ]. These findings are interesting because recent data shows that TIM-3 play a dual role: it participates in the activation of infected macrophages and negatively regulates Th1 immune response [ 45 ].…”
Section: Comparing Immunopathology In Covid-19 and Severe Influenza Imentioning
confidence: 98%
“…Kong et al assessed levels of soluble forms of checkpoint molecules in patients with COVID-19 [ 43 ]. According to the current knowledge, soluble forms may reflect the degree of membrane expression of the corresponding checkpoint proteins [ 44 ]. Kong et al found that levels of 13 out of 14 tested molecules were significantly higher in patients with severe COVID-19 than in those with mild, moderate, or asymptomatic infection [ 43 ].…”
Section: Comparing Immunopathology In Covid-19 and Severe Influenza Imentioning
confidence: 99%